Market Study for Kishorilal Shyamsunder in creating their own Scarves and Stoles brand for Indian Market - Agarwal, Deep (2016)
This dissertation provides detailed information about the current retail market scenario of India and the Indian consumer buying behaviour. It studies the market of Scarves and Stoles for KISH to develop their own brand in India.